Gene prediction for leaf margin phenotype and fruit flesh color in pineapple (Ananas comosus) using haplotype‐resolved genome sequencing. (18th March 2022) - Nashima, Kenji; Shirasawa, Kenta; Isobe, Sachiko; Urasaki, Naoya; Tarora, Kazuhiko; Irei, Ayaka; Shoda, Moriyuki; Takeuchi, Makoto; Omine, Yuta; Nishiba, Yoichi; Sugawara, Terumi; Kunihisa, Miyuki; et al.
Significance Statement: Here we report a haplotype‐resolved genome assembly of pineapple ( Ananas comosus ) 'Yugafu', a cultivar popular for fresh consumption in Japan. The study reveals AcWOX3 as the causative gene for leaf margin phenotype and AcCCD4 for fruit flesh color and carotenoid contents. SUMMARY: Pineapple ( Ananas comosus (L.) Merr.) is one of the most economically important tropical fruit species. The major aim of the breeding programs in several countries, including Japan, is quality improvement, mainly for the fresh market. 'Yugafu', a Japanese cultivar with distinctive pipe‐type leaf margin phenotype and white flesh color, is popular for fresh consumption. Therefore, genome sequencing of 'Yugafu' is expected to assist pineapple breeding. Here, we developed a haplotype‐resolved assembly for the heterozygous genome of 'Yugafu' using long‐read sequencing technology and obtained a pair of 25 pseudomolecule sequences inherited from the parental accessions 'Cream pineapple' and 'HI101'. The causative genes for leaf margin and fruit flesh color were identified. Fine mapping revealed a 162‐kb region on CLG23 for the leaf margin phenotype. In this region, 20 kb of inverted repeat was specifically observed in the 'Cream pineapple' derived allele, and the WUSCHEL‐related homeobox 3 ( AcWOX3 ) gene was predicted as the key gene for leaf margin morphogenesis. Dominantly repressed AcWOX3 via RNAi was suggested to be the cause of the pipe‐type leaf margin phenotype. Quantitative trait locus (QTL) analysis revealed that the terminal region of CLG08 contributed to white flesh and low carotenoid content. Carotenoid cleaved dioxygenase 4 ( AcCCD4 ), a key gene for carotenoid degradation underlying this QTL, was predicted as the key gene for white flesh color through expression analysis. These findings could assist in modern pineapple breeding and facilitate marker‐assisted selection for important traits.